2020
DOI: 10.1126/sciadv.abb5938
|View full text |Cite
|
Sign up to set email alerts
|

Global and local envelope protein dynamics of hepatitis C virus determine broad antibody sensitivity

Abstract: Broad antibody sensitivity differences of hepatitis C virus (HCV) isolates and their ability to persist in the presence of neutralizing antibodies (NAbs) remain poorly understood. Here, we show that polymorphisms within glycoprotein E2, including hypervariable region 1 (HVR1) and antigenic site 412 (AS412), broadly affect NAb sensitivity by shifting global envelope protein conformation dynamics between theoretical “closed,” neutralization-resistant and “open,” neutralization-sensitive states. The conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 60 publications
7
61
0
Order By: Relevance
“…The latter pathway accounts for residual infection by WT virus in the absence of SR-B1 (Figure 1B & C). Whilst this model is supported by published data (Augestad et al, 2020; Kalemera et al, 2019; Prentoe et al, 2019), the mechanistic basis of SR-B1 mediated priming has, thus far, been unclear. To recapitulate the physical reality of virus entry, the model includes a variable that reflects the intrinsic instability of HCV particles.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…The latter pathway accounts for residual infection by WT virus in the absence of SR-B1 (Figure 1B & C). Whilst this model is supported by published data (Augestad et al, 2020; Kalemera et al, 2019; Prentoe et al, 2019), the mechanistic basis of SR-B1 mediated priming has, thus far, been unclear. To recapitulate the physical reality of virus entry, the model includes a variable that reflects the intrinsic instability of HCV particles.…”
Section: Resultsmentioning
confidence: 73%
“…The precise molecular basis of E2-receptor interactions have yet to be defined at the structural level; nonetheless, mutational and antibody blocking experiments have demonstrated that SR-B1 binding occurs via the N-terminal HVR-1, whilst the CD81 binding site is thought to be composed of three discontinuous regions (antigenic site 412 [AS412], the front layer, and the CD81 binding loop) (Kong et al, 2013; Owsianka et al, 2006; Scarselli et al, 2002). Previous work, including our own, suggests that SR-B1 is the initial receptor for HCV and is likely to prime subsequent stages of entry (including interaction with CD81) via an unknown mechanism (Augestad et al, 2020; Evans et al, 2007; Kalemera et al, 2019).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations